MENGGERAKKAN EKONOMI MARITIM SYARI’AH DI INDONESIA - Said, Nur Said (EQUILIBRIUM, 2015)
This paper discusses two things: (1) The ethos of Maritime Economy in Islam, (2) Maritime Economic as the Challenges as Sharia system. Both are studied with an intertextuality approach that articulate ideas in framework of sociology of maritime in Indonesia. The conclusions are the fact that the Indonesian territory consists of75% over the sea is a part of the divine secrets that should be explored as a source of knowledge and a promising economic potential for the welfare of mankind. But in its utilization should pay attaintion to the ethical aspects with the principle holds worship (at-tawhid), equation (al-musawat), freedom (al-Hurriyat), justice (al-’adl), helping (At-ta’awun) and tolerance (at-tasamuh). It’s like have been given the common ideals of the Prophets and Apostles since Noah, Moses, Jonah and the Prophet Solomon postscript holds the principle of monotheism in interacting with nature, especially in the area of maritime in that time. Exploring the   maritime zone for human welfare is confortable as long as no monopoly, exploitation and discrimination while demanding a balance between rights and obligations. Paper ini mendikusikan dua hal: (1) Etos Ekonomi Maritim dalam Islam, (2) Ekonomi Maritim sebagai tantangan Ekonomi Syariah. Kedua bahasan tersebut dikaji dengan pendekatan intertektualitas mendialogkan berbagai ide dalam bingkai sosiologi maritim nusantara. Kesimpulan paper ini adalah semesta alam diciptakan Sang pencipta tidaklah sia-sia. Kenyataan bahwa wilayah Indonesia terdiri dari 75% lebih adalah laut adalah bagian dari rahasia ilahi yang harus digali sebagai sumber ilmu dan potensi ekonomi yang menjanjikan untuk kesejahteraan umat manusia. Namun dalam pemanfaatannya perlu memperhatikamn aspek hukum dan etika dengan memegang prinsip ibadah (at-tauhid), persamaan (al-musawat), kebebasan (al-hurriyat), keadilan (al-‘adl), tolong menolong (at-ta’âwun), dan toleransi (at- tasâmuh).  hal ini seperti telah diberikan keteladanan umum dari para Nabi dan Rasul sejak Nabi Nuh, Musa, yunus dan juga Nabi Sulaiman yang nota bene memegang prinsip tauhid dalam berinteraksi dengan